ALASAN JEPANG BELUM MERATIFIKASI BASEL BAN AMENDMENT (1993-2013) - Jelita, Irma; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research analyzes the reason of Japan has not ratify Basel Ban Amendment. Japan as a developed country has a high priority in environmental policy refused to ratify of Basel Ban Amendment. Its automatically inhibit the enactment of Basel Ban Amendment which aims to total ban on the transboundary movements of hazardous and toxic waste and other wastes that danger to human health and the environment. Japan has been a member of Basel Convention since 1993. But in reality until now Japan has remained in the position opposite party state conventions and the amendment has not been ratified. While on the other hand the Japanese continued to portray himself as pro-environment state.. Based on Porter-Brown theory, the role of actor in environments policy making, Japanese policy has not ratified the Basel Ban Amendment influenced by domestic economic interests and the influence of Japanese industrial groups in policy-making that related to the economic and industrial sectors. Japan have an interest to keep domestic economy stability after the economic bubble burst in 1993. Reduction amount of hazardous waste means reducing industrial production activity that sustain Japanese Economy. Japan also has an interest to externalization amount of waste. in addition to the economic benefits from waste trade in JEPAs, Japan also has interests to save the environment from the dangers of hazardous waste pollution. Moreover the role of industrial actor in environmental decision making also become one of causes why Japan has not ratify Basel Ban Amendment.Keywords: Convention, Ratify, Amendment, Toxic and hazardous waste, National Interest.